Novel potential lncRNA biomarker in B cells indicates essential pathogenic pathway activation in patients with SLE - Guojun Hou; Nan Shen; Zhizhong Ye; Huihua Ding; Zhihua Yin; Dai Dai; Xinyi Zhu; Yutong Zhang; Yashuo Chen; Yiwei Shen; Xiaojing Lin; Ling-Hua Zou (Lupus Science and Medicine)
Objectives Systemic lupus erythematosus (SLE) is a highly heterogeneous disease, and B cell abnormalities play a central role in the pathogenesis of SLE. Long non-coding RNAs (lncRNAs) have also been implicated in the pathogenesis of SLE. The expression of lncRNAs is finely regulated and cell-type dependent, so we aimed to identify B cell-expressing lncRNAs as biomarkers for SLE, and to explore their ability to reflect the status of SLE critical pathway and disease activity.Methods Weighted gene coexpression network analysis (WGCNA) was used to cluster B cell-expressing genes of patients with SLE into different gene modules and relate them to clinical features. Based on the results of WGCNA, candidate lncRNA levels were further explored in public bulk and single-cell RNA-sequencing data. In another independent cohort, the levels of the candidate were detected by RT-qPCR and the correlation with disease activity was analysed.Results WGCNA analysis revealed one gene module significantly correlated with clinical features, which was enriched in type I interferon (IFN) pathway. Among non-coding genes in this module, lncRNA RP11-273G15.2 was differentially expressed in all five subsets of B cells from patients with SLE compared with healthy controls and other autoimmune diseases. RT-qPCR validated that RP11-273G15.2 was highly expressed in SLE B cells and positively correlated with IFN scores (r=0.7329, p<0.0001) and disease activity (r=0.4710, p=0.0005).Conclusion RP11-273G15.2 could act as a diagnostic and disease activity monitoring biomarker for SLE, which might have the potential to guide clinical management.